Language Learning Strategies for Digital Classrooms - Li, Hao (International Journal of English Literature and Social Sciences (IJELS), 2019)
With the transitions from traditional print literacies to online multiliteracies around the world, digital learning is increasingly influencing language teaching and learning. An increasing number of students are responding more easily to interactive digital media or to digital compositions of image and sounds than they do to the traditional classrooms and texts. There is increasing pressure from teachers and learners to develop skills and knowledge needed in a digital age, and adopt new models and designs for teaching and learning. For those teachers who are willing to experiment new models and designs for teaching, it is important that they give students more time to adapt to the new method of instruction and apply appropriate management strategies to maximize their teaching effectiveness. With the aid of new age digital tools, and through technology enabled classroom strategies, students can be more active in language learning and develop communication skills and creativity.